The Relationship between Nurse's Caring Behavior and Inpatient Satisfaction Level in Tepian Baru Puskesmas Blud, East Kutai District - Witha Alfriani Lantang; Lamri B; Lukman Nulhakim (PT FORMOSA CENDEKIA GLOBAL, 2023)
Caring is central in nursing practice because caring is a dynamic approach, where a professional nurse at work must be more attentive and responsible to her client. Patient satisfaction depends on the nursing services provided by nurses, whether they are as expected or not yet. This study uses a correlation research design with a cross-sectional research design. The sample size in this study was 35 people. Statistical test results for the relationship between Caring nurses and patient satisfaction in hospitalization with the chi-square test obtained p-value = 0.028. There is a significant relationship between nurse caring and the level of patient satisfaction inpatient care at the BLUD of the Tepian Baru Health Center, East Kutai Regency.